THE ALTERNATIVE DESIGNS EFFORT TO SIMPLIFY THE NUMBER OF POLITICAL PARTIES IN INDONESIA - Sulistyani Eka Lestari; Ahmad Siboy (Jurnal Pembaharuan Hukum, 2021)
The number of political parties continues to increase from time to time. Ironically, the establishment of a political party is not based on the desire to carry out the functions of political education, political recruitment, and political regeneration. It is only to fulfill the desire for the power of a group of political elites. This research aims to analyze the need to simplify the number of political parties and determine the ideal simplification design of political parties This research used normative juridical research with statutory, historical, and conceptual approaches. The results indicated that political party simplification is needed for creating effectiveness and efficiency, minimizing segmentation or the emergence of friction among Indonesian citizens, preventing voter confusion, and maintaining political stability. Meanwhile, the ideal design to simplify political parties that can be executed is through submitting the dissolution of political parties to the Constitutional Court (Indonesian: Mahkamah Konstitusi (MK)) by expanding the criteria for those who can propose for dissolution (legal standing), imposing strict sanctions, implementing a moratorium on permits for the establishment of new parties, and extending the authority of the government to unilaterally dissolve political parties, such as the power to dissolve banned community organizations.